Custom-made acetabular implants for severe acetabular bone defects: implant evolution, mid-term clinical and radiographic outcomes, and complications in 154 consecutive patients over 18 years - Mari Babasiz; Alberto Alfieri Zellner; Tamara Babasiz; Robert Ossendorff; Frank Sebastian Fröschen; Andreas Christian Strauss; Max Jaenisch; Dieter Christian Wirtz (Arthroplasty, 2026)
Abstract Background Custom-made acetabular components (CMAC) represent an important treatment option for complex acetabular defects where standard implants are not sufficient. Over the years, substantial advances in implant design and materials have improved stability, function, and longevity of implants. However, evidence on implant survivorship and design evolution in custom-made acetabular reconstruction remains limited. Methods In this retrospective single-center study, 154 consecutive patients treated with a CMAC between October 2007 and June 2025 were analysed. All reconstructions were performed for severe acetabular defects classified as Paprosky type 3A ( n = 85) or 3B ( n = 69), corresponding to the Acetabular Defect Classification (ADC) type 3C ( n = 85) and ADC type 4 ( n = 69) with pelvic discontinuity (4A n = 14, 4B n = 28, 4C n = 27). Demographic data, implant design characteristics, and surgical technique were recorded. Clinical outcomes were assessed using the Oxford Hip Score (OHS), all complications were recorded, and radiographic evaluation was performed. Results The mean follow-up was 34.82 months (± 26.2 range, 6.2–168 months). Paired preoperative and postoperative OHS improved from 21.69 ± 5.59 to 30.93 ± 5.26, corresponding to a mean improvement of 9.23 points ( p < 0.0001). Kaplan–Meier estimated survivorship at 3 and 5 years was 0.85 (SE = 0.04) and 0.78 (SE = 0.05) for explantation and 0.64 (SE = 0.04) and 0.58 (SE = 0.05) for reoperation for any reason. Postoperative periprosthetic infection (11.0%) and dislocation (10.4%) were the most frequent complications. In an exploratory multivariable Cox model, flange design was the only covariate associated with explantation (HR 17.70, 95% CI 4.78–65.52; p < 0.001). Conclusions This 18-year single-centre experience with 154 CMAC demonstrates the mid-term clinical reliability of an individualized approach to complex acetabular reconstruction. Postoperative periprosthetic infection (11.0%) and dislocation (10.4%) remained relevant complications. The design transition from multiflange to monoflange constructs represents the principal evolution of this experience and warrants dedicated comparative evaluation.